2019
DOI: 10.1111/pcn.12940
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal GABA and glutamate levels correlate with impulsivity and cognitive function of prescription opioid addicts: A 1H‐magnetic resonance spectroscopy study

Abstract: Aim: Prescription opioids are psychoactive substances that can elicit many neuropsychological effects. There are no studies that directly demonstrate the effects of prescription opioid addiction (POA) on the human brain. This study aimed to quantify γ-aminobutyric acid (GABA) and glutamate (Glu) levels in the prefrontal cortex (PFC) of POA patients using proton magnetic resonance spectroscopy ( 1 H-MRS), and to explore their association with impulsive behavior and cognitive impairment.Methods: Thirty-five pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 52 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…Benzodiazepines and non-benzodiazepine sedative-hypnotics can change body temperature in animal models [31,32] and brain glutamine synthesis [33], but effects on brain temperature, NAA, CHO, or MI have not been reported [34]. Opioids similarly have been shown to affect brain glutamate in reward system areas [35][36][37][38], but not NAA, CHO, or MI. Two human studies have found reduced NAA in frontal gray matter in opioid addicted individuals [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepines and non-benzodiazepine sedative-hypnotics can change body temperature in animal models [31,32] and brain glutamine synthesis [33], but effects on brain temperature, NAA, CHO, or MI have not been reported [34]. Opioids similarly have been shown to affect brain glutamate in reward system areas [35][36][37][38], but not NAA, CHO, or MI. Two human studies have found reduced NAA in frontal gray matter in opioid addicted individuals [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, glutamate levels in the ACC, assessed using magnetic resonance spectroscopy (MRS), correlated positively with impulsive symptoms in subjects with attention-deficit hyperactivity disorder (ADHD) (Bauer et al, 2018;Ende et al 2016). Similar findings were found in relation to SUD using the Barratt Impulsiveness Scale (Li et al, 2020), which collectively highlight an involvement of glutamate signalling in prefrontal cortical regions in impulsive behaviour.…”
Section: Glutamatementioning
confidence: 62%
“…In the lateral OFC, but not the medial OFC, lower gene expression of the ɑ1 GABA A receptor subunit correlated with impulsive action but not impulsive choice in rats (Ucha et al, 2019). In humans, reduced MRS-GABA levels in the PFC correlated with risky and impulsive decision making (Boy et al, 2011;Weidacker et al, 2020), with Barratt Impulsiveness Scale impulsivity scores correlating negatively with MRS GABA levels in the PFC and ACC (Ende et al 2016;Li et al, 2020). Finally, reductions in GABA levels in the inferior frontal gyrus were found to underlie SSRT impulsivity (Murley et al, 2020), suggesting that multiple subtypes of impulsivity implicate diminished GABA-ergic function in several cortico-striatal regions.…”
Section: Gabamentioning
confidence: 99%
“…Brain excitement suppresses imbalance induced by γ-aminobutyric acid system dysfunction is an important mechanism for cognitive impairment [47,48]. The levels of γ-aminobutyric acid in the brain of patients with opioid addiction were significantly reduced, which was positively related to cognitive impairment [49]. Alpha-asarone, the major ingredient isolated from the Chinese medicinal herb Acorus tatarinowii Schott, can improve the cognitive function of AD rats by enhancing the γ-aminobutyric acid system, inhibiting the overexcitation of hippocampal neurons, and reducing the deposition of amyloid β-protein (Aβ) [50].…”
Section: Discussionmentioning
confidence: 99%